Role of insertion sequence Aba-1 and AdeS in reduced tigecycline susceptibility in MDR-Acinetobacter baumannii clinical isolates from Cairo, Egypt. (17th February 2018) - Hassan, Reem; Mukhtar, Ahmed; Hasanin, Ahmed; Ghaith, Doaa
Abstract : Infections caused by multidrug resistant (MDR) Acinetobacter baumannii ( A. baumannii ) especially in intensive care units have limited therapeutic options. Overexpression of the adeABC efflux pump may be caused either by the IS Aba -1 insertion or by specific point mutations in adeR and adeS, therefore, plays a major role in conferring MDR- A. baumannii. We aimed in our study to monitor the tigecycline (TGC) susceptibility and to study the role of IS Aba -1 and the adeS regulator within the AdeABC efflux pump among MDR- A. baumannii clinical isolates. MDR- A. baumannii (63) isolated from ICU patients were identified by detection of OXA-51-like gene. TGC MIC was determined by E-test and broth microdilution. PCR analysis of adeR, adeS, adeB and IS Aba 1 genes were done with further sequencing of adeS gene. Reduced susceptibility to TGC (MIC: 3–4 mg/L) was noticed in 6/63 (9.5%) MDR- A. baumannii isolates, IS Aba -1 was detected in three isolates that two of which showed amino acid substitutions in the adeS operon. We concluded that the amino acids mutations in the adeS gene in presence of insertion IS Aba -1 may play a role in conferring reduced TGC susceptibility of MDR- A. baumannii .